New theory of the Earth - Anderson, Don L (Cambridge University, 2013)
New Theory of the Earth is an interdisciplinary advanced textbook on the origin, composition, and evolution of the Earth's interior: geophysics, geochemistry, dynamics, convection, mineralogy, volcanism, energetics, and thermal history. This is the only book on the whole landscape of deep Earth processes that ties together all the strands of the subdisciplines. It is a complete update of Anderson's Theory of the Earth (1989). It includes many new sections and dozens of new figures and tables. As with the original book, this new edition will prove to be a stimulating textbook for advanced courses in geophysics, geochemistry, and planetary science, and a supplementary textbook on a wide range of other advanced Earth science courses. It will also be an essential reference and resource for all researchers in the solid Earth sciences.